2016
DOI: 10.1088/0741-3335/58/6/065002
|View full text |Cite
|
Sign up to set email alerts
|

Scrape-off layer ion temperature measurements at the divertor target during type III and type I ELMs in MAST measured by RFEA

Abstract: In future nuclear fusion reactors high heat load events, such as edge-localised modes (ELMs), can potentially damage divertor materials and release impurities into the main plasma, limiting plasma performance. The most difficult to handle are type I ELMs since they carry the largest fraction of energy from the plasma and therefore deposit the largest heat flux at the target and on first wall materials. Knowing the temperature of the ions released from ELM events is important since it determines the potential s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Divertor measurements in the low density scenario were made using a fast sweep technique (FST) where the grid 1 voltage was swept at a faster frequency of 20kHz [27]. This allowed each filament to be measured by several sweeps, each lasting 50 µs.…”
Section: Divertor Measurementsmentioning
confidence: 99%
“…Divertor measurements in the low density scenario were made using a fast sweep technique (FST) where the grid 1 voltage was swept at a faster frequency of 20kHz [27]. This allowed each filament to be measured by several sweeps, each lasting 50 µs.…”
Section: Divertor Measurementsmentioning
confidence: 99%
“…Ion temperature measurements have been made for the filaments arriving at the divertor during ELMs using an RFEA in a fast sweep mode [72]. As well as showing that the ion temperature in the filaments is much larger than the electron temperature, they have revealed that in a certain category of ELMs the filaments arrive at the target over an extended time (>1 ms), compared to the normal duration of 200-300 µs.…”
Section: Elm Physicsmentioning
confidence: 99%
“…The secondary filaments have been seen to extend the duration of the D α decay at the midplane and the ion current at the target [26]. In order to understand what effect these secondary filaments have on the heat flux profiles, a comparison of the D α duration and the duration of the target heat flux decay has been made between LSN and DND plasmas.…”
Section: Elm Database Used For Analysis Of Target Datamentioning
confidence: 99%
“…Application of this cut on the pedestal temperature produces a database of type I ELMs which con sists of 84 LSN ELMs and 15 DND ELMs. The analysis of the target footprints and timescales in LSN data can be complicated by the existence of secondary fila ments that are a result of the interaction of the ELM filaments with coils or support structures inside the vessel [26]. The sec ondary filaments have been seen to extend the duration of the D α decay at the midplane and the ion current at the target [26].…”
Section: Elm Database Used For Analysis Of Target Datamentioning
confidence: 99%